PENGUJIAN SENSOR FOTODETEKTOR SEBAGAI ALAT UKUR KADAR GULA PADA LARUTAN GULA - Taufiqurrohman Zain , Alex (Jurnal TAMBORA, 2020)
Photodiode is a type of photodetector. P-I-N (PIN) link photodiode was chosen in this study. This selection is based on high sensitivity and rapid response to any changes in light. BPW 34 type photodiode is used as a photodetector and RGB bright LED as its light source. The selection of RGB bright LEDs is based on its ability to automatically change the beam spectrum based on bit changes. As a medium for propagating light, a single mode optical fiber is used. In addition to designing hardware, this research also designs applications through Arduino IDE 1.0.4 and LabVIEW 2013 so that hardware can be controlled and displayed on a PC. As a microcontroller, the Arduino UNO module was used in this study. The results of this study indicate that the rays on the RGB bright LED can be controlled through the bit system on a PC (Personal Computer), and can bring up the measurement results of sugar content through a PC.